Development of Gamification-Based HTML5 Interactive Learning Media for Human Digestive System in Elementary Education - Sarira, Maria Jayanti; Sabariah, Sabariah; Suharti, Suharti (Jurnal Paedagogy, 2025)
This study aims to develop interactive learning media based on HTML5 with a gamification approach to improve students' understanding, activeness, and learning motivation. This research used a Research and Development (R&D) method with the ADDIE model, consisting of five main stages: analysis, design, development, implementation, and evaluation. The validation process was carried out by three experts using a feasibility assessment instrument, followed by a limited trial with fifth-grade students at SD Negeri Inpres Malompo Elementary School. Data analysis was conducted quantitatively through validation questionnaires and student responses. The findings indicated that the media was considered "very feasible" in terms of content, visual appearance, and technical aspects, and was highly effective in helping students understand the concept of digestive organs interactively. This media offers an innovative alternative in science learning in elementary schools and has the potential for further development in other materials, contributing to the development of gamification-based digital media in elementary education.